Overview of Primary Angle-Closure Glaucoma Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Mohammad Fazel Iftikhar Syahdafy; Prima Maya Sari; Fatmawati; Fidalia; Muhammad Usman Salim (Sriwijaya Journal of Ophthalmology, 2023)
Introduction: Glaucoma is a disturbance of part or all of the visual field caused by damage to the optic nerve and increased intraocular pressure, and obstruction of the outflow of aqueous humor, which causes optic neuropathy, loss of visual field, and in the final stages, can lead to complete blindness. This study aimed to provide an overview of primary angle-closure glaucoma patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This research was a descriptive observational study with secondary data, where there were 37 research subjects with 61 eyes. This study presents clinical, sociodemographic, and management data of angle-closure glaucoma patients. Data analysis was carried out univariately with SPSS. Results: The majority of angle-closure glaucoma patients are aged 40-64 years and are female. Family history with glaucoma disorders has not provided optimal data because the majority of these data are not found. The majority of glaucoma patients have intraocular pressure ≤ 21 mmHg. The majority of research subjects do not have refractive disorders. The majority of patients receive medical therapy in the form of 2-3 types of eye drops. The majority of patients are diagnosed with PACG. Conclusion: The majority of angle-closure glaucoma patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia, have normal intraocular pressure without refractive errors and receive combination therapy of 2-3 eye drops.